2010
DOI: 10.1523/jneurosci.5169-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-ErbB Signaling Promotes Microglial Proliferation and Chemotaxis Contributing to Microgliosis and Pain after Peripheral Nerve Injury

Abstract: A key component in the response of the nervous system to injury is the proliferation and switch to a "proinflammatory" phenotype by microglia (microgliosis). In situations where the blood-brain barrier is intact, microglial numbers increase via the proliferation and chemotaxis of resident microglia; however, there is limited knowledge regarding the factors mediating this response. After peripheral nerve injury, a dorsal horn microgliosis develops, which directly contributes to the development of neuropathic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
155
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(171 citation statements)
references
References 70 publications
12
155
3
1
Order By: Relevance
“…In agreement with this, treatment of chronically denervated nerve explants with recombinant NRG1 type II in the presence of forskolin increased the number of SCs migrating from the explants [97]. Furthermore, cultured peritoneal macrophages express erbB2, erbB3 and, erbB4 and in response to recombinant NRG1 β-EGF domain, show enhanced motility ( Figure 4) [98]. Therefore, in the context of peripheral nerve injury, there is some in vitro evidence that NRG1 signaling may play a role in the migration of both SCs and macrophages.…”
Section: Potential Mechanisms Of Action Of Nrg1 Signaling In Periphersupporting
confidence: 78%
See 2 more Smart Citations
“…In agreement with this, treatment of chronically denervated nerve explants with recombinant NRG1 type II in the presence of forskolin increased the number of SCs migrating from the explants [97]. Furthermore, cultured peritoneal macrophages express erbB2, erbB3 and, erbB4 and in response to recombinant NRG1 β-EGF domain, show enhanced motility ( Figure 4) [98]. Therefore, in the context of peripheral nerve injury, there is some in vitro evidence that NRG1 signaling may play a role in the migration of both SCs and macrophages.…”
Section: Potential Mechanisms Of Action Of Nrg1 Signaling In Periphersupporting
confidence: 78%
“…Reproduced with permission from [98]. Events after a peripheral nerve injury and the potential roles NRG1 may play in this process (dark boxes) (A-E).…”
Section: Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Besides, ATP is actively released from injured primary afferents and dorsal horn neurons, which induce microglial activation after binding to the microglia P2X4 receptor [10]. Another study indicated that SNL induced spinal dorsal horn microgliosis, which directly contributed to the development of neuropathic pain [45]. Microglia expressed the neuregulin 1 receptor (NRG1R), which was a growth and differentiation factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several growth and differentiation factors also sensitize nociceptors directly, as well as indirectly by allowing neurons to signal microglia and regulate cytokine release and chemotaxis of surrounding cells. These include neuregulin-1, nerve growth factor, brain-derived neurotrophic factor, and neurotrophin-3 (Polazzi and Contestabile, 2002;Calvo et al, 2010Calvo et al, , 2011. In response to nerve damage, the brain also stimulates the central cytokine cascade, activating further spinal microglia in pain-related areas and causing a positive cycle of cytokine release.…”
mentioning
confidence: 99%